2020
DOI: 10.1371/journal.pone.0234357
|View full text |Cite
|
Sign up to set email alerts
|

Gene-based analyses of the maternal genome implicate maternal effect genes as risk factors for conotruncal heart defects

Abstract: Congenital heart defects (CHDs) affect approximately 1% of newborns. Epidemiological studies have identified several genetically-mediated maternal phenotypes (e.g., pregestational diabetes, chronic hypertension) that are associated with the risk of CHDs in offspring. However, the role of the maternal genome in determining CHD risk has not been defined. We present findings from gene-level, genome-wide studies that link CHDs to maternal effect genes as well as to maternal genes related to hypertension and proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Fifth, the incidence of congenital abnormalities can vary by racial background and demonstrates at least some familial heritability. 45 , 46 Because of the racial differences in genetic factors related to alcohol metabolism as well as the onset of birth defects, 47 the findings of this study may not be applicable to non-Japanese populations. Finally, higher drinking during pregnancy can cause spontaneous abortion and stillbirth.…”
Section: Discussionmentioning
confidence: 93%
“…Fifth, the incidence of congenital abnormalities can vary by racial background and demonstrates at least some familial heritability. 45 , 46 Because of the racial differences in genetic factors related to alcohol metabolism as well as the onset of birth defects, 47 the findings of this study may not be applicable to non-Japanese populations. Finally, higher drinking during pregnancy can cause spontaneous abortion and stillbirth.…”
Section: Discussionmentioning
confidence: 93%
“…This approach is, however, limited by the relatively small size of most study cohorts, the relatively small number of additional pregnancies to each woman, and potential biases resulting from the initial ascertainment criteria (e.g., mutations identified in women who have a child with a MLID may not be associated with the full spectrum of outcomes resulting from mutations in the gene). In addition, most studies in humans have focused on rare, predicted deleterious variants in protein-coding genes, although maternal variation within non-coding regions (e.g., McJunkin 114 ) and common variation in protein-coding genes 62 , 115 , 116 may also be associated with offspring phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a genome-wide study of the association between maternal genes and conotruncal heart defects in offspring, potential MEGs were enriched by 2.3-fold (p = 0.057) among the most significantly associated (i.e., p < 0.05) maternal genes. 62 Hence, data from both model systems and humans suggest that the phenotypic spectrum for some MEGs may include structural birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pathogenic variants in PADI6 have been linked to three cases of Silver-Russell syndrome and, more recently, to several cases of Beckwith-Wiedemann syndrome (BWS, MIM 130650) (57) and generalized multilocus imprinting defects (MLID) (57,58). Genomewide studies have also found links between mothers carrying genetic variations in maternal effect genes like PADI6, and congenital heart defects (CHDs) in their offspring (59). This aggregated evidence, including data from this study, are consistent with most recent research topics in infertility, where both epidemiological and genomic investigations highlight substantial levels of biological pleiotropy, in which multiple phenotypes are influenced by a single gene or genetic network (60).…”
Section: Discussionmentioning
confidence: 99%